Protective properties of ginsenoside Rb3 against UV-B radiation-induced oxidative stress in HaCaT keratinocytes. Issue 1 (2nd January 2016) - Oh, Sun-Joo; Oh, Yuri; Ryu, In Wang; Kim, Kyunghoon; Lim, Chang-Jin
Abstract: This work aimed to evaluate the skin anti-photoaging properties of ginsenoside Rb3 (Rb3), one of the main protopanaxdiol-type ginsenosides from ginseng, in HaCaT keratinocytes. The skin anti-photoaging activity was assessed by analyzing the levels of reactive oxygen species (ROS), pro-matrix metalloproteinase-2 (proMMP-2), pro-matrix metalloproteinase-9 (proMMP-9), total glutathione (GSH), and superoxide dismutase (SOD) activity as well as cell viability in HaCaT keratinocytes under UV-B irradiation. When HaCaT keratinocytes were exposed to Rb3 prior to UV-B irradiation, Rb3 exhibited suppressive activities on UV-B-induced ROS, proMMP-2, and proMMP-9 enhancements. On the contrary, Rb3 displayed enhancing activities on UV-B-reduced total GSH and SOD activity levels. Rb3 could not interfere with cell viabilities in UV-B-irradiated HaCaT keratinocytes. Rb3 plays a protective role against UV-B-induced oxidative stress in human HaCaT keratinocytes, proposing its potential skin anti-photoaging properties. Graphical abstract: : Effects of Rb3 on the UV-B-induced proMMP-2 (A) and proMMP-9 (B) activities in conditioned media of HaCaT keratinocytes. In (C), the equal loading was shown.